1978
DOI: 10.1128/jb.133.2.942-951.1978
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Biopolyester Hydrolase (Cutinase) by Low Levels of Cutin Monomers in Fusarium solani f. sp. pisi

Abstract: Cutin hydrolysate induced the production of an extracellular cutinase by glucose-grown Fusarium solani f. sp. pisi. The rate of production depended on the amount of cutin hydrolysate added up to 80 ,ug/ml, and saturation was attained at this level. Glucose was found to be a repressor of cutinase production. A radial immunodiffusion assay for cutinase was developed, and the induction of cutinase by cutin hydrolysate was confirmed by this direct assay. When cutinase was induced by cutin hydrolysate, exogenous la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 20 publications
(21 reference statements)
1
36
0
Order By: Relevance
“…Earlier studies with F. solani f. sp. pisi showed that induction of cutinase occurred in cultures supplied with 0.25 to 0.5 g l 31 powdered apple cutin [4] or smaller amounts (0.08 g l 31 ) of a hydrolysate prepared from the apple cutin or cutin monomers and their analogues such as a C 16 alcohol [19]. In our work we found that the C 16 alcohol, hexadecanol, was not as e¡ective as an inducer of cutinolytic activity in MPV strains as it was in MPVI strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies with F. solani f. sp. pisi showed that induction of cutinase occurred in cultures supplied with 0.25 to 0.5 g l 31 powdered apple cutin [4] or smaller amounts (0.08 g l 31 ) of a hydrolysate prepared from the apple cutin or cutin monomers and their analogues such as a C 16 alcohol [19]. In our work we found that the C 16 alcohol, hexadecanol, was not as e¡ective as an inducer of cutinolytic activity in MPV strains as it was in MPVI strains.…”
Section: Discussionmentioning
confidence: 99%
“…The mating behaviour of the isolates was previously established by mating with known`tester' strains [18]. Although we were primarily interested in the two cucurbit pathogens (MPI and MPV), strains of the pea pathogen MPVI were included to provide a comparison since most of the knowledge on cutinase activity in N. haematococca has come from a study of that group [5,14,15,19]. A total of 11 MPI, four MPV and six MPVI isolates was studied.…”
Section: Fungal Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case oi F. solani f. sp. pisi, cutinase was also induced by cutin fatty acids (LIN and KOLATTUKUDY 1978, WoLOSHUK and KOLATTUKUDY 1986, PODILA et al 1988. In the present work, we used commercial fatty acids as carbon source for A. pisi, and showed that juniperic acid is a good inducer of the in vitro release of esterase activity by this fungus.…”
Section: Discussionmentioning
confidence: 62%
“…Cutinase is known to be induced in fungi by using cutin as sole source of carbon. Fungal cutinase was also induced by low concentrations of fatty acids extracted from hydrolyzed cutin (LIN and KOLATTUKUDY 1978, WOEOSHUK and KOLATTUKUDY 1986, PODILA et al 1988; its activity was severely inhibited by reagents directed towards active serine, such as diisopropyl fluorophosphate (DFPJ (PuRDY and KOLATTUKUDY 1975).…”
mentioning
confidence: 99%